KONTRIBUSI INFLASI SEBAGAI MODERASI RETURN ON ASSET (ROA) CURRENT RATIO (CR) SERTA DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR KEUANGAN DI BEI - Makmur, Munandar; P, Mappamiring; Akob, Rezki Arianty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test and analyze the relationship between Inflation moderation between Return On Asset (ROA), Current Ratio (CR) and Debt To Equity Ratio (DER) to stock returns in financial sector companies on the IDX. The type of research used is a quantitative approach, the population in this study is the banking subsector listed on the Indonesia Stock Exchange (IDX) for the 2021 - 2023 period as many as 47, the sampling technique uses the purposive judgement sampling method with a sample of 39 companies, the number of data units analyzed is 132. Hypothesis testing uses panel data regression analysis and MRA. The results of the analysis provide evidence that ROA has a significant positive effect on Stock Returns, CR has a positive effect on Stock Returns, DER has a significant negative effect on Stock Returns, Inflation has a significant negative effect on Stock Returns, Inflation is proven to weaken the relationship between ROA and Stock Returns, Inflation cannot moderate the relationship between CR and Stock Returns, Inflation is proven to strengthen the relationship between DER and Stock Returns